Cells are us - Balkwill, Frances R.; Rolph, Mic (Minneapolis : Carolrhoda Books, 1993)
Explains the functions of cells in the human body, including the role that DNA and chromosomes play in the life and functioning of cells.
Appraisal-Science Books for Young People.
School Library Journal.
Wilson's Children.
5.5.
5.5
3-6
Keywords: Cell differentiation -- Juvenile literature; Cells -- Juvenile literature; Cell differentiation; Cells; Cell differentiation; Cells